ANALYSIS OF CRYPTOCURRENCY AS INVESTMENT ASSET IN OPTIMIZING THE PORTFOLIO PERFORMANCE (CASE STUDY: PT MANDIRI MANAJEMEN INVESTASI) - Dewa Gede Rama, I
Cryptocurrency is one of the most disruptive innovation that continuously emerge from reinvention of digital currency to revolution of transaction mechanism. The ease and efficiency offered by the cryptocurrency makes it an alternative currency for some parties. The high fluctuation in cryptocurrency prices raises the idea that these assets have a high level of risk, which is ultimately expected to provide high return as well. By considering the cryptocurrency as a digital asset, and understanding its growing value as an opportunity, the cryptocurrency can be considered as one of the instruments that can be used to optimize the portfolio performance. In this study, a set of performance comparison analysis was carried out on portfolio that only involves common assets and portfolio with a number of cryptocurrency in it. Performance measurement was carried out based on the Sharpe ratio, and portfolio optimization was carried out using the Markowitz method. Efficient frontier was also used as an analytical tool in determining the portfolio efficiency. The obtained results and findings state that portfolio with cryptocurrencies in its composition suggests a higher risk and return potential. Through the Markowitz method, the portfolio Sharpe ratio can be optimized up to 20 times at 26.35% by the indexed cryptocurrencies, and up to 59 times at 76.11% by the individual cryptocurrencies. CRYPTO5 index contributed with rate of return at 148.98%, as well as individual BTC, ETH, XRP, and XMR respectively contributed with rate of return at 168.77%, 234.25%, 562.86%, and 422.13%. The optimal compositions of cryptocurrency mixed portfolio for risk averse investor is 5.02% of LQ45, 85.37% of FIFI, and 9.61% of CRYPTO5. While the optimal compositions of the cryptocurrency mixed portfolio for risk seeking investor is 83.06% of BTC, 4.87% of ETH, 1.49% of XRP, and 10.57% of XMR.